"A merry heart doeth good like a medicine": humour, religion and wellbeing - Collicutt, Joanna (Mental health, religion & culture, 2012)
This essay explores the relationship between humour, religion, and wellbeing. It surveys some historical and contemporary psychological approaches to humour, and examines the empirical findings on the relationship between humour and health. It notes the historical antipathy between religion and humour, and argues that this is based on an incomplete analysis of the complexities of both religion and humour, including the chronological aspects of phase in the life of a religion or religious movement, and the capacity of humour both to conserve and subvert received wisdom of the faith tradition. Finally, it argues that aspects of both humour and religion are associated with transcendence, and that this maybe a helpful a conceptual bridge linking the two.